Arthroscopic versus mini-open rotator cuff repair: A meta-analysis. Issue 1 (February 2023) - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Joerg; Schenker, Hanno; Tingart, Markus; Betsch, Marcel
Abstract: Background: An all-arthroscopic rotator cuff repair (ASR) may result in less postoperative pain and better functional outcomes than the mini-open (MOR) approach. This meta-analysis provides an updated assessment of the current literature which compares the clinical outcomes of mini-open versus all arthroscopic rotator cuff repair techniques. Material and methods: The main online databases were accessed in October 2021. All the trials directly comparing primary ASR versus MOR for rotator cuff rupture were accessed. Studies concerning revision settings were not eligible, nor where those combining the surgical procedures with other adjuvants. Results: A total of 21 articles were retrieved. Data from 1644 procedures (ASR = 995, MOR = 649) were collected. The mean follow-up was 26.7 (6.0–56.4) months. Comparability was found between ASR and MOR groups at baseline with regards to age (P = 0.3), gender (P = 0.7) and mean duration of the follow-up (P = 0.7). No difference was found between ASR and MOR with regard to surgical duration (P = 0.05), Constant score (P = 0.2), University of California at Los Angeles Shoulder (P = 0.3), American Shoulder and Elbow Surgeons Shoulder (P = 0.5), VAS (P = 0.2), forward flexion (P = 0.3), abduction (P = 0.3), external rotation (P = 0.2), internal rotation (P = 0.7), re-tear (P = 0.9), adhesive capsulitis (P = 0.5). Conclusion: Arthroscopic and mini-open rotator cuff repair result in similar clinical outcomes. Male gender and older age lead to greater rates of rotator cuff re-tears, while longer surgical duration was associated with a greater rate of adhesive capsulitis.